Development of Two New Spectrophotometeric Methods for the Determination of Amitriptyline in Pharmaceutical Preparation Using Univariate and Simplex Optimization - Mohammed, A. k . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two simple and sensitive spectrophotometric methods are proposed for the determination of amitriptyline in its pure form and in tablets. The first method is based on the formation of charge- transfer complex between amitriptyline as n-donor and tetracyano-ethylene (TCNE) as Ï€acceptor. The product exhibit absorbance maximum at 470 nm in acetonitrile solvent (pH =9.0 ) . In the second method the absorbance of the ion- pair complex, which is formed between the soughted drug and bromocresol green (BCG), was measured at 415 nm at ( pH=3.5) . In addition to classical univariate optimization, modified simplex method (MSM) was applied in the optimization of the variable affecting  the color producing reaction by a geometric simplex in three dimensions of space.  Beers, law was obeyed in the concentration ranges 6.0-70  and 8.0-100 Âµg.ml-1 with molar absorbitivites of 2275 and 1475 l. mol-1 cm-1 for TCNE and BCG methods respectively. The limits of detection of the two methods are 0.043 and 0.034 Âµg.ml-1 and their Sandells sensitivity values are 0.122 and 0.188 Âµg.ml-1 respectively.